Profitability Analysis of Home-scale SMEs Based on Digital Marketing Media - Clara Herlina Karjo; Bertha Elvy Napitupulu; Francisca Hermawan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Home-scale business or doing business from home by family members is one choice to sustain people’s economy during the covid pandemic. With the advance of digital technologies, these home-scale businesses should be performed through digital platforms or social media. With proper utilisation, social media can increase the profits of these businesses. The purpose of this article is to analyse how social media can generate profit for small scale businesses. The data were obtained from the sales reports of three home-scale businesses in Jakarta, which specialized in selling traditional snacks. From the data, we analyzed the profit earned from each of the social media used (Instagram, Facebook, WhatsApp, and Word of Mouth) to find out which media generated the most profit for their business. We found that the highest profit for home scale business came from Instagram because promotion through Instagram resulted in the highest number of items sold. The findings signify that using the right social media can generate maximum profit. However, the use of social media as digital marketing tool should depend on the habits and control of the business owner over the media.